Comparison of Two Different Intraoral Scanners for Determination of Caries Related Volume Loss in Caries Removal - Şeker, Merve; Alkan, Elif; Tağtekin, Dilek; Korkut, Bora; Yanıkoğlu, Funda (Journal of Dentistry Indonesia, 2023)
Objective: The study aimed to compare cavity volume data obtained with two different intraoral scanners. Methods: One hundred extracted molar teeth were divided into groups according to ICDAS-II classification, and scanned with Cerec Omnicam (Dentsply Sirona) and iTero Element Flex (Align Technology). The caries-infected tissues were removed regarding either minimally invasive or conventional cavity principles. Samples were scanned again and volumetric data were assessed by Meshmixer 3.5 (Autodesk) 3D modeling software. Statistical evaluations were performed with Mann Whitney U test and Spearman’s Correlation test. The significance level was α=0.05. Results: Although there was a significant difference between obtained initial volume readings of two scanners for 3M and 3C groups (p < 0.05), no significant difference was observed among other groups (p ≥ 0.05). Regarding the comparison of final volume readings of two scanners, a significant difference was found for 5M group (p = 0.036), whereas no significant difference was observed for other groups (p ≥ 0.05). Percentage of volume loss between two scanners was statistically similar (p ≥ 0.05). Conclusion: Data obtained with Cerec Omnicam and iTero Element Flex were compatible with volumetric assessments. Both intraoral scanners may be considered effective for calculating caries-related cavity volumes. Minimally invasive cavity principles may provide less volume loss compared to conventional cavity principles.